2013
DOI: 10.1155/2013/754580
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania majorSelf-Limited Infection Increases Blood Cholesterol and Promotes Atherosclerosis Development

Abstract: Leishmania major infection of resistant mice causes a self-limited lesion characterized by macrophage activation and a Th1 proinflammatory response. Atherosclerosis is an inflammatory disease involving hypercholesterolemia and macrophage activation. In this study, we evaluated the influence of L. major infection on the development of atherosclerosis using atherosclerosis-susceptible apolipoprotein E-deficient (apoE KO) mice. After 6 weeks of infection, apoE KO mice exhibited reduced footpad swelling and parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Finally, mouse models (Fernandes et al, 2013;Ghosh, Bose, Roy, & Bhattacharyya, 2013;Ghosh et al, 2012;Shamshiev et al, 2007) and epidemiological data (Ghosh et al, 2011;Lal et al, 2007;Soares et al, 2010) suggest a correlation between hypocholesterolemia and hypolipidemia and progression of the disease. However, the kinetics and mechanism (s) leading to alterations in cholesterol distribution in host cell membranes, its extent, and effect on its biosynthesis are still not understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, mouse models (Fernandes et al, 2013;Ghosh, Bose, Roy, & Bhattacharyya, 2013;Ghosh et al, 2012;Shamshiev et al, 2007) and epidemiological data (Ghosh et al, 2011;Lal et al, 2007;Soares et al, 2010) suggest a correlation between hypocholesterolemia and hypolipidemia and progression of the disease. However, the kinetics and mechanism (s) leading to alterations in cholesterol distribution in host cell membranes, its extent, and effect on its biosynthesis are still not understood.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic studies of the host cells showed that Leishmania infection modulated the expression of genes associated with cholesterol biosynthesis, uptake, and efflux (Osorio y Fortea et al., ; Rabhi et al., ). Finally, mouse models (Fernandes et al., ; Ghosh, Bose, Roy, & Bhattacharyya, ; Ghosh et al., ; Shamshiev et al., ) and epidemiological data (Ghosh et al., ; Lal et al., ; Soares et al., ) suggest a correlation between hypocholesterolemia and hypolipidemia and progression of the disease. However, the kinetics and mechanism (s) leading to alterations in cholesterol distribution in host cell membranes, its extent, and effect on its biosynthesis are still not understood.…”
Section: Introductionmentioning
confidence: 99%
“…GSEA analysis also revealed that patients with obstructive CAD with higher expression levels of NCF2, MYO1F, S1PR4, and FCN1 in PBMC showed enriched pathways in viral myocarditis, Leishmania infection, type I diabetes mellitus, and hematopoietic cell lineage. These pathways are critical for the development of atherosclerosis and CADs . Since more than 65% of STEMI patients suffer from obstructive CAD, it is presumable that this four‐gene signature could also be developed as a potential prognostic biomarker of obstructive CAD occurrence in STEMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways are critical for the development of atherosclerosis and CADs. [25][26][27] Since more than 65% of STEMI patients suffer from obstructive CAD, 23,24 it is presumable that this four-gene signature could also be developed as a potential prognostic biomarker of obstructive CAD occurrence in STEMI patients. However, this warrants another separate study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are consequences of the stimulation of the immune system by L. major, which promotes the inflammatory components of atherosclerosis, which are primarily the parasiteactivated macrophages [35]. Several studies suggest that pathogenic bacteria, viruses and protozoa, contribute to the atherogenesis process [36,37,38,39,40].…”
Section: Fig 2 Lesion Sizes Of Balb/c Mice Infected With L Major and Feed With Rp And Afpp On 12 Weeksmentioning
confidence: 99%